Possible interbreeding in late Italian Neanderthals? New data from the Mezzena jaw (Monti Lessini, Verona, Italy). - Silvana Condemi (Public Library of Science (PLoS), 2013)
In this article we examine the mandible of Riparo Mezzena a Middle Paleolithic rockshelter in the Monti Lessini (NE Italy, Verona) found in 1957 in association with Charentian Mousterian lithic assemblages. Mitochondrial DNA analysis performed on this jaw and on other cranial fragments found at the same stratigraphic level has led to the identification of the only genetically typed Neanderthal of the Italian peninsula and has confirmed through direct dating that it belongs to a late Neanderthal. Our aim here is to re-evaluate the taxonomic affinities of the Mezzena mandible in a wide comparative framework using both comparative morphology and geometric morphometrics. The comparative sample includes mid-Pleistocene fossils, Neanderthals and anatomically modern humans. This study of the Mezzena jaw shows that the chin region is similar to that of other late Neanderthals which display a much more modern morphology with an incipient mental trigone (e.g. Spy 1, La Ferrassie, Saint-Césaire). In our view, this change in morphology among late Neanderthals supports the hypothesis of anatomical change of late Neanderthals and the hypothesis of a certain degree of interbreeding with AMHs that, as the dating shows, was already present in the European territory. Our observations on the chin of the Mezzena mandible lead us to support a non abrupt phylogenetic transition for this period in Europe.